Characterization of a brown bear aggregation during the hyperphagia period in the Cantabrian Mountains, NW Spain - Ruíz-Villar, Héctor; Morales-González, Ana; Bombieri, Giulia; Zarzo-Arias, Alejandra; Penteriani, Vincenzo (Ursus, 2019)
We characterized a brown bear (Ursus arctos) feeding aggregation that occurred in an oak (Quercus spp.) forest in the Cantabrian Mountains (NW Spain), during the hyperphagia period 2017 (Sep to Dec), which was an atypical year in terms of low fructification success due to late frost events and drought. We described (1) number, sex, and age class of aggregated bears; (2) temporal use of the area; and (3) bear interactions. We identified a minimum of 31 individuals, representing 10% of the estimated Cantabrian bear population. The number of adults increased during the study period, whereas the number of subadults decreased, which could be related to a displacement of subadults by dominant adults. The proximity of the aggregation site to a public road attracted numerous people to observe the bears. To minimize adverse bear-human interactions, we recommend providing educational material on best bear-viewing practices as well as on-site staffing. VP was financially supported by the Excellence Project CGL2017-82782-P financed by the Spanish Ministry of Science, Innovation and Universities, the Agencia Estatal de Investigación (AEI), and the Fondo Europeo de Desarrollo Regional (FEDER, EU). Peer Reviewed